The Effects of the Management of Natural Energy Resources in the European Union - VORONENKO, Viacheslav; KOVALOV, Bohdan; HOROBCHENKO, Denys; HRYCENKO, Pavlo (Journal of Environmental Management and Tourism; Vol 8 No 7 (2017): JEMT Volume VIII Issue 7(23) Winter 2017DO - 10.14505//jemt.v8.7(23).10, 2018)
This paper is devoted to the study of the impact of the management of natural energy resources on sustainable development and green growth. The object of the study is the process of management of natural energy resources. An indicator of adjusted net savings was used to estimate sustainable development. The performed comparative analysis of the adjusted net savings without subtraction and subtraction of the costs of extracting energy natural resources as a result of the synthesis shows a significant difference. It is on average for 2012-2016 is 4% of gross national income for the whole world. When subtracting production costs, the adjusted net savings will be much smaller and this fact must be taken into account. In order to simultaneously take into account the economic situation of the country, the depletion of energy resources, their consumption, and the consequence of consumption, relevant indicators are proposed, as well as a special index for estimating the changes over time. The results of the study show that most countries in the European Union have positive adjusted energy and carbon efficiency, since they are higher than global measures. In addition, the relationship between carbon efficiency and energy efficiency in these countries is still very close. The analysis of changes in time as a result of synthesis also showed positive results, according to which the adjusted energy efficiency in most countries of the European Union is growing. According to the high growth rates of this indicator, some countries have a good opportunity to make significant progress in green growth, although this may require expensive investments.